PENGARUH MEDIA TALI TEMALI TERHADAP KETERAMPILAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK AISYIYAH DESA KARANGAN TINGGI KECAMATAN TAMBANG KABUPATEN KAMPAR - Susi Rahayu; Zulkifli N '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the results of field observations of the fine motor skills of the students is still low and teachers are still teaching methods that dominate and not varied. So we need a media application rigging .This study aims to determine the effect of media rigging the fine motor skills of children aged 5-6 years in kindergarten Aisyiyah High Authorship Village District of Kampar Regency Mines. The sample used in this study were 15 children. The data collection techniques were used that observation. The study hypothesis fine motor skills of the students after applying rigging media also shows the results of analysis of data obtained t = 16.412 and P = 0.000 . Because p ˂ 0.05 it can be concluded that there are differences in fine motor skills of the students were very significantly after use of media in learning the ropes . So Ho rejected and Ha accepted which means no significant difference between before and after performing experiments by applying media rigging . The hypothesis test can be seen hitung =16.412 > t tabel = 1,761. So it means that Ho is rejected and Ha accepted. It can be known from the value of P= 14